Imprints of the secondary interstellar hydrogen atoms at 1 au. Issue 2 (6th April 2021) - Katushkina, O A; Baliukin, I I; Izmodenov, V V; Alexashov, D B
ABSTRACT: In this paper, we search for the possible imprints of the secondary interstellar hydrogen atoms created at the heliospheric boundary in the full-sky maps of the hydrogen fluxes at the Earth orbit. By using our three-dimensional time-dependent kinetic model, the maps of the hydrogen fluxes are calculated for different phases of the solar cycle and different energy ranges. It is shown that the flux maps obtained during the solar minimum conditions for the energy range 1–20 eV have specific features such as blobs and tails, which are pronounced due to a signal of the secondary component of the interstellar atoms. We investigate how these features depend on parameters of the secondary atoms far away from the Sun and found that the geometry and shape of the tails depend on the averaged velocity and kinetic temperatures of the secondary population. The results of the paper provide a strategy where and when we need to look in order to detect the secondary component of the interstellar hydrogen separately from the primary component at 1 au . This can be important for future space missions devoted to the exploration of the heliospheric boundary.